Perception and definition of artistic craft within cultural and creative industries based on the qualitative data analysis - Rydvalová, Petra; Michalová, Tereza; Škaloudová Puchmajerová, Lucrezia (Creativity Studies, 2025)
Culture and creativity are integral to European cultural and creative industries, pivotal in shaping Europe’s identity and global prominence. The focus on crafts within the cultural and creative industries ecosystem underscores their cultural significance. However, classifying crafts as artistic or traditional needs more systematic indicators. This article addresses this gap by proposing a methodology to evaluate the artistry of crafts. Twelve indicators were identified based on literature and in-depth interviews with Czech craft organizations to evaluate the artistry of the particular craft. Chosen respondents (legal entities and natural persons) self-evaluated these indicators, assigning weights based on importance. Results revealed varying weights, with mastery of the craft and originality deemed most significant. The proposed methodology offers a scalable approach to determining the artistry of crafts and aiding enterprises and policymakers in supporting cultural and creative industries. This study contributes to theory as well as practice by providing a comprehensive framework for identifying and evaluating artistic craftsmanship within the cultural and creative industries.